'Don't Even Think About Bringing That to School': New Brunswick students' understandings of ethnic diversity. (July 2018) - Hamm, Lyle; Peck, Carla L; Sears, Alan
Canada is a country with a long history of substantial ethnocultural diversity. Questions about the reasonable accommodation of immigrant groups, the preservation of official language minority rights, and the fostering of Aboriginal rights permeate political and social discourse in Canada. Effective citizenship requires people who understand the subtle differences between and among groups in Canada, and are able to wrestle intelligently and respectfully with difficult questions inherent in these issues. This article reports on a study designed to map the conceptions of ethnic diversity held by grade 6 students in the eastern Canadian province of New Brunswick with a particular focus on the three areas outlined above. Overall, students demonstrated quite superficial understandings of ethnic diversity being able to identify some practices and beliefs as 'cultural', but with little knowledge of specific cultural groups or practices or the role of language as a vehicle for cultural enhancement and preservation.